Identification and preliminary evaluation of polychlorinated naphthalene emissions from hot dip galvanizing plants. (January 2015) - Liu, Guorui; Lv, Pu; Jiang, Xiaoxu; Nie, Zhiqiang; Liu, Wenbin; Zheng, Minghui
Highlights: Hot dip galvanizing was found to be a source of polychlorinated naphthalenes. PCN emission factors in solid residues from hot dip galvanizing were derived. Congeners CN37/33/34, CN52/60, CN66/67, and CN73 were dominant in their respective homologs. Hot dip galvanizing might not be a priority for controlling PCN release. Abstract: Hot dip galvanizing (HDG) processes are sources of polychlorinated- p -dioxins and dibenzofurans (PCDD/Fs). Close correlations have been found between the concentration of PCDD/Fs and polychlorinated naphthalenes (PCNs) that are produced and released during industrial thermal processes. We speculated, therefore, that HDG plants are potential PCN sources. In this preliminary study, PCNs were analyzed in solid residues, ash and precipitate from three HDG plants of different sizes. The total PCN concentrations (∑2–8 PCNs) in the residue samples ranged from 60.3 to 226 pg g −1 . The PCN emission factors for the combined ash and precipitate residues from the HDG plants ranged from 75 to 178 ng t −1 for the dichlorinated and octachlorinated naphthalenes. The preliminary results suggested that the HDG industry might not currently be a significant source of PCN emissions. The trichloronaphthalenes were the dominant homologs followed by the dichloronaphthalenes and the tetrachloronaphthalenes. The PCN congeners CN37/33/34, CN52/60, CN66/67, and CN73 dominated the tetrachlorinated, pentachlorinated, hexachlorinated, and heptachlorinated naphthalene homologs, respectively. The PCNs emitted from the HDG plants had similar homolog distributions and congener profiles to the PCNs emitted from combustion plants and other metallurgical processes. The identification and preliminary evaluation of PCN emissions from HDG plants presented here will help in the prioritization of measures for controlling PCN emissions from industrial sources.